Generation differences in importance perception of productive ageing and the validity analysis of productive ageing scale - Rie, Juil; Kang, Younwook; Kim, Jihyun; Ryu, Kyung (Korean Journal of Industrial and Organizational Psychology, 2011)
This study has two purposes. One is to identify generation differences in importance perception of productive ageing. Second is to find relationship between productive ageing and successful ageing. First, we developed 20 items to measure productive activities based on Caro, Bass, & Chen (1993)’s definition. Our items were divided into 4 factors; to do activities for life goals, to do activities for self career development, to do activities for family assistance, and to do volunteering activities. In our research, we found generation differences in importance perception of productive activities for successful ageing. In comparison with the elderly, younger people considered it more important to do activities for life goals, career development, and volunteering in their old age. Productive ageing scale of 20 items newly developed for this study was divided into 4 factors in our confirmatory factor analysis, and the reliability of 4 sub-scales was good. The importance perception of productive ageing was significantly related with subjective wellbeing and life meaning. Even after controlling personality such as extroversions, conscientiousness, and openness, it explained significantly subjective wellbeing and life meaning. Lastly, working elderly and non-working elderly were different in meaning perception about productive ageing. Working elderly considered it important to do activities for life goals.